Peran Pendidikan Anti-Korupsi dalam Membangun Karakter Mahasiswa di Institut Ilmu Al-Qur'an An-Nur Yogyakarta - Ningsi, Ayu; Yunianta, Rohmat Dwi; Sabaruddin, Sabaruddin; Khamid, Nur Al (Universitas Indraprasta PGRI Jakarta, 2024)
This study analyzes and explores the role of anti-corruption education in shaping character and raising anti-corruption awareness among students, as well as identifying the challenges in integrating anti-corruption values at Institut Ilmu Al-Qur'an An-Nur Yogyakarta. Students are seen as potential agents of change in the fight against corruption, but they need to be equipped with a deep understanding of the dangers of corruption and the importance of integrity in social life. The aim of this research is to analyze the role of anti-corruption education in building student character at Institut Ilmu Al-Qur'an An-Nur Yogyakarta. This study uses a descriptive qualitative method with an observational and interview-based approach. The results indicate that anti-corruption education is effective in shaping student character and increasing anti-corruption awareness in higher education environments. Concrete steps, such as integrating anti-corruption values into the curriculum and providing active moral guidance, can significantly contribute to building a more dignified and integral generation. Students not only have theoretical knowledge of corruption but are also capable of implementing anti-corruption values through real actions around them, both on campus and in the broader community.